Marital Quality: Analysis on Couples Who Have Long-Distance Marriages - Kmas M. Eka Fhitrah; Afdal Afdal (Universitas Negeri Padang, 2020)
Couples who undergo a long-distance marriage face more challenges than those who undergo an ordinary marriage so that they will be more prone to conflicts resulting in low quality of marriage relationships, low quality of marital relationships that can lead to divorce. This research method uses a quantitative approach with a comparative descriptive method. The subjects in this study were couples who were undergoing a long-distance marriage in Padang City. The research subjects were taken using a purposive technique so that the number of research subjects was 120 consisting of 60 male partners and 60 female partners. The research instrument for the quality of the marriage relationship used a Likert scale model adapted from the PBSC measuring instrument from Ducat & Zimmer-Gembeck (2010) with reliability of 0.923. The findings of the study show that: (1) On average, the marital quality of couples who are undergoing a long-distance marriage for men is in the medium category and women is in the medium category. (2) There is no significant difference in marital quality in terms of gender (3) There is no significant difference in marital quality in terms of the type of work.